Stock control: a study on stock management efficiency in a wholesale distributor in Divinópolis-MG (Research, Society and Development, 2018)
The goal of this paper is to identify the most appropriate tools, and how they can increase the efficiency of stock management in a wholesalemicroenterprise, which operates in the refrigerated food sector in Divinópolis, MG. A descriptive research with a qualitative approach was carried out through a case study. The data were collected by direct observation of the work routine of the company's warehouse, documentary research and semi-structured interview with the warehouse manager and the dispatcher. It was observed that the main weaknesses of this management are the lack of control of quantity of goods in stock, deteriorated goods with expired validity, lost sales due to lack of goods and merchandise without the necessary care. Therefore, it was concluded that the use of tools such as the ABC curve, physical inventory, Peps and the establishment of demand level will contribute to increase the efficiency of inventory management.